2020
DOI: 10.3390/cancers12082083
|View full text |Cite
|
Sign up to set email alerts
|

Stromal CCL2 Signaling Promotes Mammary Tumor Fibrosis through Recruitment of Myeloid-Lineage Cells

Abstract: Obesity is correlated with breast tumor desmoplasia, leading to diminished chemotherapy response and disease-free survival. Obesity causes chronic, macrophage-driven inflammation within breast tissue, initiated by chemokine ligand 2 (CCL2) signaling from adipose stromal cells. To understand how CCL2-induced inflammation alters breast tumor pathology, we transplanted oncogenically transformed human breast epithelial cells with breast stromal cells expressing CCL2 or empty vector into murine mammary glands and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 107 publications
1
28
0
Order By: Relevance
“…Early recruitment of macrophages is correlated with cancer initiation, which includes formation of a favorable TME. CAF recruitment and fibrosis stroma formation in tumors are also dependent on macrophage recruitment ( 98 ). The role of fibroblasts in the early progression of ductal carcinoma in situ remains to be explored.…”
Section: Tumor-associated Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early recruitment of macrophages is correlated with cancer initiation, which includes formation of a favorable TME. CAF recruitment and fibrosis stroma formation in tumors are also dependent on macrophage recruitment ( 98 ). The role of fibroblasts in the early progression of ductal carcinoma in situ remains to be explored.…”
Section: Tumor-associated Stromal Cellsmentioning
confidence: 99%
“…Infiltration of adipose stromal cells into in tumor tissue enhance CCL2 production, contributing to more recruitment of myeloid-lineage cells ( 98 ). Uchiyama et al.…”
Section: Tumor-associated Stromal Cellsmentioning
confidence: 99%
“…Also, the overexpression of CCL2 by breast stromal cells transplanted into mouse mammary glands leads to enhanced TAM infiltration, concomitant with increased collagen expression. Both of these effects were ablated by depletion of CD11b expressing cells ( 30 ). These data suggest that tumors can manipulate the CCL2/CCR2 pathway to facilitate the infiltration of tumor prone collagen-producing macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neutralization experiments using anti-IL-6 or CCL2 antibodies have demonstrated that the migration enhancing effect of CAA-conditioned media can be abolished ( 15 ). A recent study has determined that chronic inflammation induced by CCL2 can significantly promote tumor growth and connective tissue matrix formation via the early entry of macrophages and fibroblasts into the TME ( 137 ).…”
Section: Adipokinesmentioning
confidence: 99%